Evaluation of Organizational Culture As a Step To Improve Patient Safety at RSIGMP Sultan Agung Semarang - Gesti Bening Aulia; Kusuma Arbianti; Nira Ardlina (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
This study assessed and evaluated organizational culture to improve RSIGMP Sultan Agung Semarang patient safety. This observational analytic study used a cross-sectional model. Data were collected by distributing questionnaires of the Organizational Culture Assessment Instrument (OCAI) to all RSIGMP Sultan Agung Semarang staff, with a total of 54 people. The questionnaire was previously tested for validity and reliability. It consisted of 24 statements from 10 dimensions of organizational culture (dominant characteristics, organizational leadership, management of employees, organizational glue, strategic emphasis, and criteria for success). The study results showed that the dominant type of culture at RSIGMP Sultan Agung Semarang was clan culture.